Gambaran Pengetahuan Penderita Gastritis tentang Gastritis Di Desa Koto Perambahan Wilayah Kerja Puskesmas Kampa - Nurul Latifa Anum; Dewi Anggriani Harahap; Indrawati Indrawati (Institute of Advanced Knowledge and Science, 2026)
Gastritis is a non-communicable disease with a high incidence in Indonesia, including in Kampar Regency. Public knowledge about gastritis is an important factor in preventing and managing this disease. This study aims to determine the knowledge of gastritis patients in Koto Perambahan Village, the working area of ​​the Puskesmas Kampa in 2024. This study used a quantitative descriptive design with a sample of 55 gastritis patients selected using a simple random sampling technique. The instrument used was a questionnaire. The data were analyzed univariately and presented in the form of frequency distributions and percentages. The results showed that 22 respondents (40%) had good knowledge, while 33 respondents (60%) had poor knowledge about gastritis. It is recommended to provide regular health education to the public, especially gastritis sufferers, to increase knowledge and encourage preventive behaviors to prevent complications